Innovation-led value chain management in mango and banana - Damodaran, T; Beer, Karma; Ravi, S C; Mishra, Maneesh; Shukla, P K; Singh, Akath (Indian Horticulture, 2026)
Among fruit crops, mango and bananas are the most important crops hovering 50% share in fruits area substantially dominated by mango. Fruit crops production witnessed significant increase from 28.6 million metric tonne (MMT) in 1991–92 to 118.76 MMT in 2024-25. Subtropical production, however, faces distinct constraints: variable climates, short and uneven fruiting periods, cultivar-specific postharvest sensitivity, and fragmented, small holder based value chains that depress farm-gate prices and heighten losses. Persistent gaps include limited pre- and postharvest technologies suited to subtropical cultivars, weak cold-chain and controlled-atmosphere capacity, inadequate extension and aggregation services, inconsistent grading standards, low uptake of processing, and poor market information and finance access. The production and processing for premium markets faced stringent competition from the imports. These challenges arise from biological factors, infrastructure deficits, seasonal gluts, and limited product diversification. ICAR CISH developed innovation led solutions in value chain management of mango, banana and honey with four interoperable pillars: (1) improved on-farm interventions— canopy management, bagging of fruits, IPM based biointensive pest disease management system; (2) cost-effective postharvest options—low cost precooling, better packaging, modular cold-chains, and basic ethylene and decay control; (3) value addition—community processing, standardized grading, aggregation models, and quality/ origin branding; and (4) enabling systems—capacity building, cooperatives, inclusive finance, and digital market information. An implementation roadmap emphasizes scalable pilots, public–private partnerships, and gender-responsive approaches to reduce losses and raise incomes.